Digestibility and stability of ultrasound-treated fish oil emulsions prepared by water-soluble bitter almond gum glycated with caseinate. (August 2021) - Rahimi, Parisa; Hosseini, Ebrahim; Rousta, Esmat; Bostar, Habibe
Abstract: This study aimed to investigate the influence of the water-soluble fraction of bitter almond gum (SBAG), sodium caseinate (SC), and their conjugate on the physicochemical stability and gastrointestinal fate of ultrasound-mediated fish oils-in-water emulsions. The conjugate-based emulsion exhibited the same physical stability as the SC-stabilized counterpart. They were remarkably more stable against the aggregation at cold storage than ambient temperature. Overall, SBAG-based emulsion had better oxidative stability than other emulsions. Oil droplet size was significantly increased during in vitro digestion compared to the initial emulsions ( P  < 0.05). The extent of FFA released from the SBAG-stabilized emulsion was higher than other emulsions, indicating that the fish oil lipolysis was performed better with pancreatic lipase in the presence of SBAG. The results suggest that simultaneous application of SBAG and its conjugate may be an appropriate way to improve the oxidative and physical stability of lipophilic compounds in functional foods and beverages. Graphical abstract: Image 1 Highlights: The soluble phase of bitter almond gum (SBAG) reduced oil oxidation of emulsion. The conjugation process improved the physical stability of SBAG in emulsion. SBAG provided more lipid digestibility than sodium caseinate in the emulsion. SBAG and its conjugate can be a novel carrier to deliver lipophilic compounds.